Performance characterization of Ni60-WC coating on steel processed with supersonic laser deposition - LUPOI, ROCCO (My University, 2015)
Ni60-WC particles are used to improve the wear resistance of hard-facing steel due to their high hardness. An emerging technology that combines laser with cold spraying to deposit the hard-facing coatings is known as supersonic laser deposition. In this study, Ni60-WC is deposited on low-carbon steel using SLD. The microstructure and performance of the coatings are investigated through SEM, optical microscopy, EDS, XRD, microhardness and pin-on-disc wear tests. The experimental results of the coating processed with the optimal parameters are compared to those of the coating deposited using laser cladding.
PUBLISHED
Keywords: Ni60-WC; Supersonic laser deposition; Laser cladding; Microstructure; Wear; Nanoscience & Materials